Labor Market Slack and the Output Gap : The Case of Korea - Hansen, Niels-Jakob (IMF Working Papers; Working Paper ;, 2019)
Output gap estimates are widely used to inform macroeconomic policy decisions, including in Korea. The main determinant of these estimates is the measure of labor market slack. The traditional measure of unemployment in Korea yields an incomplete estimate of labor market slack, given that many workers prefer involuntary part-time jobs or leaving the labor force rather than registering as unemployed. This paper discusses a way in which the measure of unemployment can be broadened to yield a more accurate measure of labor market slack. This broader measure is then used to estimate the output gap using a multivariate filter, yielding a more meaningful measure of the output gap.